2000
DOI: 10.1046/j.1365-2222.2000.00800.x
|View full text |Cite
|
Sign up to set email alerts
|

Farm environment in childhood prevents the development of allergies

Abstract: Childhood farm environment seems to have a protective effect against allergic rhinitis and/or conjunctivitis, and more weakly against asthma and wheezing irrespective of family size. Environmental exposure to immune modulating agents, such as environmental mycobacteria and actinomycetes, favouring manifestation of a nonatopic phenotype could explain the finding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
220
7
8

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 325 publications
(259 citation statements)
references
References 39 publications
24
220
7
8
Order By: Relevance
“…Estimates from the video questionnaire for the prevalence of wheeze in the previous 12 months were even lower, ranging 1.3-3.3% for the centres in China, whereas the global mean was 7.3%. The low prevalence of asthma-like symptoms and reported asthma in rural areas in China is consistent with recent reports of the scarcity of asthma and atopy among children raised on farms in several countries [7][8][9][10][11]. It has been postulated that the lifestyle associated with living on a farm (larger family size, more pets, heating frequently using wood or coal, less maternal smoking and more dampness) may be responsible for the low prevalence.…”
Section: Discussionsupporting
confidence: 85%
“…Estimates from the video questionnaire for the prevalence of wheeze in the previous 12 months were even lower, ranging 1.3-3.3% for the centres in China, whereas the global mean was 7.3%. The low prevalence of asthma-like symptoms and reported asthma in rural areas in China is consistent with recent reports of the scarcity of asthma and atopy among children raised on farms in several countries [7][8][9][10][11]. It has been postulated that the lifestyle associated with living on a farm (larger family size, more pets, heating frequently using wood or coal, less maternal smoking and more dampness) may be responsible for the low prevalence.…”
Section: Discussionsupporting
confidence: 85%
“…In previous studies, socioeconomic status, dwelling place and mother's parity were shown to be associated with atopic disorders [25][26][27] and depression. [28][29][30] Therefore, dwelling place and father's social class in 1966, as well as mother's parity, were evaluated as potential confounding variables.…”
Section: Confounding Variablesmentioning
confidence: 91%
“…For instance, in the traffic exposure-response study by Montnémery et al (114) (Table 2), although there were significant associations of asthma symptoms and diagnosis to traffic density, there were no urban-rural differences. In addition, some recent studies that specifically examined farming environments, found a decreased risk of asthma and atopy among children living on farms (137,138), particularly where there is regular contact with farm animals. This prompted these investigators to hypothesize that a "protective farm factor" may reflect the influence of microbial agents on T H 1 versus T H 2 cell development or reflect the development of immunotolerance (137,138).…”
Section: Coherence With Traffic Studies By Trends In Asthma and Urbanmentioning
confidence: 99%
“…In addition, some recent studies that specifically examined farming environments, found a decreased risk of asthma and atopy among children living on farms (137,138), particularly where there is regular contact with farm animals. This prompted these investigators to hypothesize that a "protective farm factor" may reflect the influence of microbial agents on T H 1 versus T H 2 cell development or reflect the development of immunotolerance (137,138). This possibility, in addition to potentially high levels of confounding by uncontrolled factors that vary by geography, makes it difficult to clearly interpret the cross-sectional studies on urban versus rural areas or ecologic studies of international differences.…”
Section: Coherence With Traffic Studies By Trends In Asthma and Urbanmentioning
confidence: 99%